2022
DOI: 10.3389/fpls.2022.819282
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Transcriptome Indicators of Salt Tolerance in Wild and Cultivated Barley

Abstract: Barley is used as a model cereal to decipher salt tolerance mechanisms due to its simpler genome than wheat and enhanced salt tolerance compared to rice and wheat. In the present study, RNA-Seq based transcriptomic profiles were compared between salt-tolerant wild (Hordeum spontaneum, genotype no. 395) genotype and salt-sensitive cultivated (H. vulgare, ‘Mona’ cultivar) subjected to salt stress (300 mM NaCl) and control (0 mM NaCl) conditions. Plant growth and physiological attributes were also evaluated in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 85 publications
(111 reference statements)
0
14
1
Order By: Relevance
“…Phenolic compounds, including anthocyanin and melanin pigments, that can by synthesized in hulls and pericarp of barley grain, play diverse biochemical and molecular functions in plant physiology ( Treutter, 2006 ; Vogt, 2010 ; Kiani et al, 2021 ; Gharaghanipor et al, 2022 ). They are not only protect the seeds from damage, deterioration, and pest but also are beneficial to human health ( Rasouli et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenolic compounds, including anthocyanin and melanin pigments, that can by synthesized in hulls and pericarp of barley grain, play diverse biochemical and molecular functions in plant physiology ( Treutter, 2006 ; Vogt, 2010 ; Kiani et al, 2021 ; Gharaghanipor et al, 2022 ). They are not only protect the seeds from damage, deterioration, and pest but also are beneficial to human health ( Rasouli et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…They represent a very diverse class of plant secondary metabolites, derived from phenylalanine, and play a vital role in plant physiology. These compounds are essential structural components of cell walls, protect plants against various biotic and abiotic environmental factors, act as phytoalexins against herbivores and pathogens, and—because some of them are pigments—mediate interactions of plants with pollinators and seed dispersers ( Treutter, 2006 ; Vogt, 2010 ; Kiani et al, 2021 ; Gharaghanipor et al, 2022 ). Synthesis of all phenylpropanoids starts with the conversion of phenylalanine (or tyrosine) originating from the shikimate pathway by phenylalanine ammonia lyase (PAL; or tyrosine ammonia lyase, TAL), cinnamate 4-hydroxylase (C4H), and 4-coumaroyl coenzyme A (CoA) ligase (4CL) into p -coumaroyl-CoA, which is a precursor for all subsequent pathway branches and resulting metabolites including benzoic acids, flavonoids, monolignols, stilbenes, and coumarins ( Vogt, 2010 ; Deng and Lu, 2017 ; Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, expression co-reaction network analysis revealed that some DEGs playing various functions (e.g., genes associated with ABA signaling or lipid catabolism) had similar regulation under drought and under its combination with heat; on the other hand, the coincident expression of such DEGs was observed between heat and control conditions. Interestingly, among them, there were DEGs related to oxidoreductases that showed contrasting behavior, i.e., some were overexpressed and others were downregulated under D and HD in relation to H and C. It would seem that oxidoreductase-related genes should be generally upregulated in response to stressors, as indicated by Gharaghanipor et al (2022), who observed increased abundance of oxidoreductase-coding transcripts in stress-sensitive barley genotypes under salinity. Also, Szurman-Zubrzycka et al ( 2021) identified massive upregulation of peroxidases encoding genes in barley roots under low pH.…”
mentioning
confidence: 99%
“…RNA-sequencing (RNA-seq) is an efficient and less expensive next-generation sequencing (NGS) method that has broad applications, including the identification of differentially expressed genes and determining pathways in crops grown under different stress (Khatiwada et al, 1996;Mattiello et al, 2010;Xu et al, 2017;Gharaghanipor et al, 2022). There has been no published transcriptome-based research on Al-tolerance in finger millet to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%